2007
DOI: 10.2164/jandrol.106.000216
|View full text |Cite
|
Sign up to set email alerts
|

Relative Levels of Semen Platelet Activating Factor‐Receptor (PAFr) and Ubiquitin in Yearling Bulls With High Content of Semen White Blood Cells: Implications for Breeding Soundness Evaluation

Abstract: High content of the platelet activating factor (PAF) and its plasma membrane receptor (PAFr) in semen is thought to benefit fertility in farm animals and humans. We used flow cytometric, biochemical, and immunocytochemical analysis to examine PAFr levels alone (Trial 1, n 5 156 bulls) or in a dual assay with sperm defect marker ubiquitin (UBI; Trial 2, n 5 88 bulls), in semen samples from 160 yearling bulls undergoing Breeding Soundness Evaluations (BSE). In both trials, we observed increased PAFr levels in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…The tg338 mouse line has been proved to be able to detect infectivity in a tissue with less than 1/5000 brain infectivity, which is equivalent to sensitivity within the picogram range of Prp sc per milligram of tissue (Andreoletti et al 2004). Our results demonstrated that the transmission of scrapie did not occur with semen from infected rams at any point during scrapie incubation, even with a highly infected animal such as the oldest VRQ/VRQ ram that was sampled at the clinical stage and when spermatozoa and seminal plasma (and also cells and organelles that can be found within this fluid , Sutovsky et al 2007) contain undetectable levels of infectivity. This absence of infectivity in sheep semen may reflect the lack of transconformation of the prion protein in the genital tract due to either the specific biochemical properties of the different glycosylated and truncated forms present (Shaked et al 1999, Ecroyd et al 2005 or the high level of protection formed by the testicular and epididymal blood barrier (Cyr et al 2007).…”
Section: Prpmentioning
confidence: 61%
“…The tg338 mouse line has been proved to be able to detect infectivity in a tissue with less than 1/5000 brain infectivity, which is equivalent to sensitivity within the picogram range of Prp sc per milligram of tissue (Andreoletti et al 2004). Our results demonstrated that the transmission of scrapie did not occur with semen from infected rams at any point during scrapie incubation, even with a highly infected animal such as the oldest VRQ/VRQ ram that was sampled at the clinical stage and when spermatozoa and seminal plasma (and also cells and organelles that can be found within this fluid , Sutovsky et al 2007) contain undetectable levels of infectivity. This absence of infectivity in sheep semen may reflect the lack of transconformation of the prion protein in the genital tract due to either the specific biochemical properties of the different glycosylated and truncated forms present (Shaked et al 1999, Ecroyd et al 2005 or the high level of protection formed by the testicular and epididymal blood barrier (Cyr et al 2007).…”
Section: Prpmentioning
confidence: 61%
“…Acquired relative intensities of TRITC labeling were plotted as histograms and divided into three areas of low (marker area M1), medium (marker area M2) and high relative intensity (marker area M3; see Figure 1A, 1B ), essentially as described for ubiquitin, PAFR and 15-LOX proteins in animal spermatozoa [35], [36]. The marker area M1 contains the low-fluorescent sperm fragments and debris.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated semen ubiquitin content correlates with fertility outcomes and conventional semen parameters in humans and animals, and can be measured by FC using anti-ubiquitin antibodies 43 48 and fluorochromes with affinity to aggresomes, 44 the cellular stress-induced aggregates of nonrecycled ubiquitinated proteins most likely of spermiogenic origin. In domestic bull, sperm surface ubiquitination correlates positively with DNA damage 43 and frequency of acrosomal damage 49 and negatively with conventional semen parameters (sperm count, sperm motility, % normal morphology) and scrotal circumference, 8 as well as with conception rates in AI service. 44 Increased white blood cell contamination revealed by immunolabeling of PAFR correlated positively with semen ubiquitin level in breeding bulls undergoing breeding soundness evaluation but the sperm surface expression of PAFR actually appeared diminished in ubiquitinated spermatozoa.…”
Section: Ubiquitin and Ubiquitin-like Protein Modifiersmentioning
confidence: 99%
“…Ubiquitinated bull spermatozoa display increased sperm DNA fragmentation detectable by TUNEL assay, 43 as well as increased affinity for lentil agglutinin Lens culinaris agglutinin (LCA) 44 and a lack of surface platelet activating factor receptor (PAFR), 8 altogether suggestive of possible apoptotic and/or oxidative damage to sperm plasma membrane. Coating with lysine-rich ubiquitin may give the defective spermatozoa and sperm fragments a positive charge to promote their agglutination.…”
Section: Ubiquitin and Ubiquitin-like Protein Modifiersmentioning
confidence: 99%
See 1 more Smart Citation